Volatile compounds of vegetarian soybean kapi, a fermented Thai food condiment - Suttida Wittanalai (2018)
Kapi is a traditional shrimp paste used as a food condiment in Thailand. Several vegetarian soybean kapi, S1-S5, were fermented from various bacterial starter cultures isolated from commercial shrimp paste. The volatile compounds of S1-S5 were analyzed using SPME coupled with gas chromatography/mass spectrometry and compared to three samples of commercial vegetarian kapi (J1- J3) and commercial shrimp pastes (K1-K3). 124 volatile compounds consisting of aldehydes, alcohols, ketones, acids and esters, N-containing compounds, aromatic compounds, S-containing compounds, miscellaneous, indoles and hydrocarbons were identified. Principle component analysis and cluster analysis separated the volatile profile of the fermented samples into four groups. Vegetarian soybean kapi, S1, S4 and S5 produced from Bacillus subtilis IS4, TISTR10 and TISTR1, respectively, were classified into the following groups containing commercial kapi (J1, J2, K2 and K3), that had a predominance of indole, S-containing and N-containing compounds. Sensory evaluation of S1 showed a strong kapi odor with higher scores among the vegetarian soybean kapi and there were no significant differences in evaluation scores between S1 and commercial vegetarian kapi J1-J3. These data demonstrate that B. subtilis IS4 can be employed as a starter culture to produce an acceptable vegetarian soybean kapi substitute for shrimp paste kapi. © 2011 Academic Journals.